Evidence for a negative cooperativity between eIF5A and eEF2 on binding to the ribosome - Rossi, Danuza [UNESP]; Barbosa, Natalia M. [UNESP]; Galvão, Fabio C. [UNESP]; Boldrin, Paulo E. G. [UNESP]; Hershey, John W. B.; Zanelli, Cleslei F. [UNESP]; Fraser, Christopher S.; Valentini, Sandro R. [UNESP] (Public Library of Science (PLoS), 2016)
eIF5A is the only protein known to contain the essential and unique amino acid residue hypusine. eIF5A functions in both translation initiation due to its stimulation of methionyl-puromycin synthesis and translation elongation, being highly required for peptide-bound formation of specific ribosome stalling sequences such as poly-proline. The functional interaction between eIF5A, tRNA, and eEF2 on the surface of the ribosome is further clarified herein. Fluorescence anisotropy assays were performed to determine the affinity of eIF5A to different ribosomal complexes and reveal its interaction exclusively and directly with the 60S ribosomal subunit in a hypusine-dependent manner 60S-eIF5A-Hypi 60S-eIF5A-Lysi = 385 nM). A 3-fold increase in eIF5A affinity to the 80S is observed upon Meti binding, indicating positive cooperativity between P-site tRNA binding and eIF5A binding to the ribosome. Previously identified conditional mutants of yeast eIF5A, eIF5AQ22H/L93F and eIF5AK56A ,display a significant decrease in ribosome binding affinity. Binding affinity between ribosome and eIF5A-wild type or mutants eIF5AK56A ,butnoteIF5AQ22H/L93F , is impaired in the presence of eEF2 by 4-fold, consistent with negative cooperativity between eEF2 and eIF5A binding to the ribosome. Interestingly, high-copy eEF2 is toxic only to eIF5AQ22H/L93F and causes translation elongation defects in this mutant. These results suggest that binding of eEF2 to the ribosome alters its conformation, resulting in a weakened affinity of eIF5A and impairment of this interplay compromises cell growth due to translation elongation defects.